SOSIALISASI BAHAYA NAPZA (NARKOTIKA, ALKOHOL, PSIKTROPIKA DAN ZAT ADIKTIF LAINNYA) DI UPT SMP NEGERI 1 KAHU - Wahyuningsih, Wahyuningsih; AR, Amran; Hadijah Wahid, St. (LP2M Universitas Islam Ahmad Dahlan, 2022)
This KKNP is a forum and a vehicle for students of the Islamic Religious Institute of Muhammadiyah Sinjai to carry out the chess dharma of higher education, especially the third dharma, namely community service. Based on observations on Thursday, February 10, 2022, information was obtained from the kelurahan regarding a general explanation of the organization in the Palattae ward, both regarding the number of neighborhoods in the kelurahan, community conditions, educational conditions, development of foreign workers/TPA and community entrepreneurship. From the results of the survey that has been carried out, many people still do not understand the risks of the dangers of drugs, especially for students as the nation's young generation. The importance of providing understanding to students about the dangers of drugs, which is the initial foundation and formation of children's character to refuse drugs.